Bimtek Penyusunan Rencana Pelaksanaan Pembelajaran Berbasis Kurikulum Merdeka Belajar untuk Guru di Sekolah Dasar - Nellitawati Nellitawati; Ermita Ermita; Nur Hazizah; Tia Ayu Ningrum (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Solok is one of the areas in the Province of West Sumatra, Indonesia which is in a very strategic location, located at the intersection of roads between provinces and between districts/cities in West Sumatra. However, the results of the Solok City teacher competency test in 2020 are still low. Coupled with the existence of an independent learning policy that makes teachers and policy makers nervous. This is because many teachers do not understand how to prepare RPP (learning implementation plans) based on independent learning policies and their teaching materials. And for this region there has been no training for teachers on the preparation of lesson plans and teaching materials based on the independent learning policy.The solution to overcome this problem is to conduct training and direct guidance on the preparation of lesson plans and teaching materials based on independent learning policies for teachers. The technical guidance carried out involves education and learning experts. First, will be the transfer of knowledge about the policy of independent learning to teachers. Furthermore, the teachers will be guided and assisted to make plans for implementing learning and teaching materials based on independent learning. In this technical guidance, teachers will also be guided to be able to integrate technology in content creation, find teaching materials online, get interactive learning media used for learning implementation plans as guidelines in carrying out learning. lesson plans and semester learning plans.